2017
DOI: 10.1097/sap.0000000000001031
|View full text |Cite
|
Sign up to set email alerts
|

The Sternum-Nipple Distance is Double the Nipple-Inframammary Fold Distance in Macromastia

Abstract: In our series, the N-IMF distance increased 0.45 cm for every 1 cm increase in the SN-N distance. This relationship strengthens our primary hypothesis that the lower pole ligaments stretch at a significantly slower rate than the upper pole ligaments. Taking this into consideration, we suggest that surgeons seeking to minimize pseudoptosis rates should favor techniques that minimally disrupt the lower SL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…21 A small selection of studies incorporated multiple pedicles. 17,19,21 The mean follow-up across all studies was 19.5 (±13.5) months. The focus of this study was on complication rates, with NAC necrosis as the primary factor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 A small selection of studies incorporated multiple pedicles. 17,19,21 The mean follow-up across all studies was 19.5 (±13.5) months. The focus of this study was on complication rates, with NAC necrosis as the primary factor.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age and BMI of the study population was 39.2 ± 5.6 and 32.9 ± 3.4, respectively. Eleven studies 4,10–19 included smoking history as a comorbidity and found that 0% to 56.5% were active smokers or claimed a history of tobacco use 12,15 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This nipple displacement may be explained by changes in the ligamentous anatomy. 9,10 Matousek et al 9 reported that the breast is globally surrounded by taut ligaments. The medial breast ligaments are short and taut compared with the lateral ligaments, and hence, in some patients, as the breast enlarges, the nipple is displaced medially from the breast meridian.…”
Section: Discussionmentioning
confidence: 99%
“…Steele et al 3 studied the comparative strength of the upper and lower breast pole suspensory ligaments with proxies for upper and lower suspensory ligament strength and found that sternal notch-to-nipple distance was double Once duplicates from different databases were removed, 39 articles remained. Of these, 19 articles were excluded from the review.…”
Section: Intraglandular Fascia and Ligaments Cooper Ligamentsmentioning
confidence: 99%